2020
DOI: 10.3389/fcell.2020.00036
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Human Induced Pluripotent Stem Cells for Cardiac Repair

Abstract: The paracrine effect, mediated by chemical signals that induce a physiological response on neighboring cells in the same tissue, is an important regenerative mechanism for stem cell-based therapy. Exosomes are cell-secreted nanovesicles (50-120 nm) of endosomal origin, and have been demonstrated to be a major contributor to the observed stem cell-mediated paracrine effect in the cardiac repair process. Following cardiac injury, exosomes deriving from exogenous stem cells have been shown to regulate cell apopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 100 publications
1
22
0
Order By: Relevance
“…Recent studies confirmed that exosomes repaired tissue damage and inhibited tissue degeneration by inhibiting apoptosis and inflammation 41‐44 . Based on the GO analysis of proteins carried in exosomes, we also found that N‐Exos may inhibit IVDD by inhibiting NPC apoptosis.…”
Section: Discussionsupporting
confidence: 57%
“…Recent studies confirmed that exosomes repaired tissue damage and inhibited tissue degeneration by inhibiting apoptosis and inflammation 41‐44 . Based on the GO analysis of proteins carried in exosomes, we also found that N‐Exos may inhibit IVDD by inhibiting NPC apoptosis.…”
Section: Discussionsupporting
confidence: 57%
“…34 Accumulating evidence suggests exosomes secreted from different cell types carry vast different varieties of bioactive molecular cargoes and subsequently provide different biological responses. 35 For instance, exosomes secreted from human CD34 + stem cells, which were isolated from peripheral blood mononuclear cells, promoted the repair of the ischemic hindlimb. 28 The exosomes derived from CD34 + cells contain proangiogenic miRNAs, such as miR-126-3p, which enhance angiogenesis by regulating the expression of pro-angiogenic genes, including VEGF, angiopoietins, and matrix metallopeptidase 9.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated that MSC stimulates neovascularization and blood perfusion in ischemic tissues by secreting pro‐angiogenic cytokines and growth factors, including VEGF, FGF‐2, HGF, and IGF‐1 34 . Accumulating evidence suggests exosomes secreted from different cell types carry vast different varieties of bioactive molecular cargoes and subsequently provide different biological responses 35 . For instance, exosomes secreted from human CD34 + stem cells, which were isolated from peripheral blood mononuclear cells, promoted the repair of the ischemic hindlimb 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Other Stem Cell-Derived Exosomes. Exosomes secreted by induced pluripotent stem (iPS) cells protect the heart against multiple stress [61]. iPS cell-derived exosomes enhance the autophagic flux by inhibiting mTOR pathway and promoting cardiomyocyte survival both in vitro and in vivo [62].…”
Section: Biomed Research Internationalmentioning
confidence: 99%